Dosimetric influence of deformable image registration uncertainties on propagated structures for online daily adaptive proton therapy of lung cancer patients. (June 2021) - Nenoff, Lena; Matter, Michael; Amaya, Enrique Javier; Josipovic, Mirjana; Knopf, Antje-Christin; Lomax, Antony John; Persson, Gitte F; Ribeiro, Cássia O; Visser, Sabine; Walser, Marc; Weber, Damien Charles; Zhang, Ye; et al.
Highlights: Daily adaptive proton therapy is beneficial even if optimized on uncorrected, propagated structures. There is no systematic difference between rigid or deformable image registration for structure propagation in online daily adaptive proton therapy. A careful structure review should be done offline and corrections can be included in an offline adaption. Abstract: Purpose: A major burden of introducing an online daily adaptive proton therapy (DAPT) workflow is the time and resources needed to correct the daily propagated contours. In this study, we evaluated the dosimetric impact of neglecting the online correction of the propagated contours in a DAPT workflow. Material and methods: For five NSCLC patients with nine repeated deep-inspiration breath-hold CTs, proton therapy plans were optimised on the planning CT to deliver 60 Gy-RBE in 30 fractions. All repeated CTs were registered with six different clinically used deformable image registration (DIR) algorithms to the corresponding planning CT. Structures were propagated rigidly and with each DIR algorithm and reference structures were contoured on each repeated CT. DAPT plans were optimised with the uncorrected, propagated structures ( propagated DAPT doses ) and on the reference structures ( ideal DAPT doses ), non-adapted doses were recalculated on all repeated CTs. Results: Due to anatomical changes occurring during the therapy, the clinical target volume (CTV) coverage of the non-adapted doses reduces on average by 9.7% (V95) compared to an ideal DAPT doses . For the propagated DAPT doses, the CTV coverage was always restored (average differences in the CTV V95 < 1% compared to the ideal DAPT doses ). Hotspots were always reduced with any DAPT approach. Conclusion: For the patients presented here, a benefit of online DAPT was shown, even if the daily optimisation is based on propagated structures with some residual uncertainties. However, a careful (offline) structure review is necessary and corrections can be included in an offline adaption.